GEMA DI WAKTU SUBUH - Yogi Elga Rianggi; Rafiloza Rafiloza; Wilma Sriwulan (Melayu Arts and Performance Journal, 2019)
ABSTRACTGema di Waktu Subuh (in English, it’s translated into Echo at the Dawn Time) is the work of multimedia music with the method of sound exploration in the form of sound-design composition. This composition consists of manipulative sounds that describe the atmosphere occurring at the time of Subuh prayer in Salayo Tanang Bukit Sileh, Lembang Jaya sub-district, Solok district. This composition includes in illustration music that explores the sounds of nature at dawn such as river sound, cicada’s sound, rooster’s sound, vehicle sound, the sound of people’s reciting verses in Quran, and Shalawat Tahrim as the sign of the entrance of Subuh prayer time. Gema di Waktu Subuh was processed through the application of Digital Audio Workstation (DAW) cubase5 with the assistance of Virtual Sound Technology (VST) namely Waves 9, processed with producing 3d sound. Keywords: Multimedia Music, Manipulation, Exploration, Breaking Dawn Echo.  ABSTRAKGema di Waktu Subuh merupakan karya musik multimedia dengan metode eksplorasi bunyi dalam bentuk penggarapan Sound Design. Karya ini merupakan suara-suara manipulasi yang menggambarkan suasana yang terjadi ketika akan masuknya waktu sholat subuh di daerah Salayo Tanang Bukit Sileh Kecamatan Lembang Jaya Kabupaten Solok .Karya ini termasuk musik ilustrasi mengeksplorasi suara-suara Alam diwaktu  subuh, seperti: bunyi sungai, bunyi jangkrik, bunyi ayam berkokok, bunyi kendaraan, bunyi orang yang membacakan Tilawah ayat suci Al-Qur’an, dan Shalawat Tahrim sebagai penanda masuknya waktu sholat Subuh.Gema di Waktu Subuh diolah melalui sarana pengaplikasian Digital Audio Workstation (DAW) cubase5 dengan bantuan Virtual Sound Technology (VST) yaitu Waves 9, diolah dengan menghasilkansuara 3d sound. Kata kunci: Musik-Multimedia, Manipulasi, Eksplorasi, Gema-Shubuh.